Short range ordering improves elastic properties of Mo additive W-Re solid solution: A first principles investigation. (February 2023) - Bao, S.; Guo, X.W.; Wang, Z.L.; Zhao, Q.; Liu, Y.L.; Meng, F.S.; Sun, B.Z.; Jia, N.; Qi, Y.
Abstract: Re can significantly improve the ductility of W, while it is prone to form clusters and intermetallic phases, leading to instability and brittleness of W. To explore better ways to inhibit the adverse effects, we explored combined effect of Mo and alloying order on the phase stability and mechanical properties of W-Re alloys by using the first principles method. It is found that the short range ordered (SRO) W-Re structure is softer than that of random and ideal solid solution alloys. While SRO W-Mo-Re structure possesses higher stability and strength than those of random distributed alloys. The SRO W-Mo-Re structure can promote the coherent bonding enhancement between W, Mo and Re. This study shed light on better design of alloy additions and control of alloy orders to modulate the softening and strengthening properties in W and W-Re alloys, especially to reduce the hardening and instability induced by Re rich clusters. Graphical abstract: Image, graphical abstract